Fenomeni di mobilità tra esercito, curie e burocrazia nella legislazione di Valentiniano I - Bernier, Andrea (Cultura giuridica e diritto vivente, 2020)
[Mobility between Army, City Senates and Bureaucracy in the Legislation of the Emperor Valentinian] In the later Roman empire, the sons of soldiers were legally compelled to follow in their father's footsteps. However, several laws of Valentinian I from the years 371-2 show how in practice the constraints were far less rigid than the imperial constitutions themselves prescribed. Sons of veterans are attested within the city senates or in service in the offices of the bureaucracy; likewise, officiales made their entry into the army. The imperial chancellery recognized the legitimacy of some of these situations which, while contradicting the principle of the inheritance of the function, had to prove advantageous for the same authority.